Influence of anionic species on the low temperature pyrolysis performance of heated tobacco sheets catalyzed by sodium salts - Zhao, Xuebin; Wang, Qiuling; Ai, Dan; Tian, Haiying; Zhang, Zhan; Cao, Ke; Wang, Yixuan; Qi, Wei; Li, Bo; Niu, Yapeng; Meng, Lingchuang; Gao, Beibei; et al. (Frontiers in Chemistry, 2024)
The low temperature pyrolysis performances of heated tobacco sheets catalyzed by various anionic sodium salts were investigated using TG-DTG, Py-GC-MS technology and smoke routine chemical composition analysis. The results showed that the total weight loss between 100-300 °C increased by 7.8% -13.15% after adding various anionic sodium salts, among which, sodium acetate and sodium tartrate showed a relatively higher weight loss. The relative content of free hydroxyacetone, furfuryl alcohol, butyrolactone and megastigmatrienone in the pyrolysis gas increased, while the relative content of free nicotine decreased. With the change of anionic species, the catalytic decomposition ability of cellulose, lignin, and other substances may change, resulting in the distribution alteration of compounds in the pyrolysis gas. After adding sodium acetate and sodium citrate, the release of total particulate matter (TPM), glycerol, and nicotine in flue gas increased. Overall, the addition of sodium acetate and sodium citrate showed a higher low temperature pyrolysis performance of heated tobacco sheets. The research results in this paper provide data support for changing the low temperature catalytic pyrolysis performance of heated tobacco sheets by adjusting the type of anions in sodium salts.